Representing organization knowledge, management, and the information age - Lilley, Simon (Oxford University Press, 2004)
This text is an attempt to bridge the gap between the abstractions of current theories of organization and the somewhat excessively grounded material that forms the bulk of literatures within the information systems and knowledge management communities.